An alternative moral ontology in a pluralistic, post-apartheid society - Compaan, AL (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
This article is a reading of the work of the well-known Reformed theologian, Dirkie Smit, to help Reformed churches in South Africa to reorientate them in a new, complex and pluralistic social environment. After considering the conceptualisation of pluralism in recent academic and theological debates, I examine Smit’s reading of the impact of pluralism on Reformed churches in South Africa after apartheid and why these churches, in his opinion, no longer play a meaningful role in the present reconstruction of South African society. In the latter part of the article Smit’s understanding of the liturgy as an “alternative moral ontology,” creating alternative moral communities and identities, will be used to illuminate the future public role of churches in our complex, pluralistic society.